Is potential output growth falling? - Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2017)
We document differences between the evolution of a measure of potential output growth and the evolution of a measure of potential output per capita growth using time-varying parameter models estimated for four advanced economies (Canada, Germany, the United Kingdom and the United States). The evidence supports the view that most of the slowdown in potential output growth occurred prior to the Great Recession. However, the potential output per capita growth rate: 1) remained relatively constant in Canada; and 2) decreased less (more) than the potential output growth rate in Germany and the United States (in the United Kingdom). These results indicate that: 1) the decline in potential output growth in Canada is mainly associated with the decrease in population growth; and 2) the decrease in population growth is an important factor in order to explain the decline in potential output in Germany and the United States, but not in the United Kingdom.
Keywords: O41; O47; 330; Potential output growth rate; Potential output per capita growth rate; Rates of growth consistent with a constant unemployment rate